Makna Kemenangan dan Kekalahan dalam Permainan Olahraga Menurut Siswa Sekolah Dasar - Izat Hatami (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Language is a social phenomenon that reflects values, beliefs, and cultural practices within a community. In the context of sports games in elementary schools, the meanings of “winning” and “losing” are not merely competitive outcomes but also represent social and moral constructs shaped through interaction. A sociolinguistic perspective enables deeper understanding of how students interpret and express these meanings in social contexts.This article aims to examine how sociolinguistic approaches can be implemented in language learning to explore elementary students’ understanding of winning and losing in sports games and to analyze their impact on communicative competence.This study employed a descriptive qualitative design using a literature review approach. Data were collected through systematic searches and analysis of academic documents (journal articles, books, and conference proceedings) from databases such as Google Scholar. The data were analyzed using thematic content analysis to identify recurring patterns, key concepts, and significant findings.The findings indicate that sociolinguistic approaches can be implemented through authentic discourse analysis, role-play simulations, and discussions of language variation. These strategies enhance students’ understanding of language variation, register, politeness, and context-appropriate language use. Furthermore, such approaches improve students’ pragmatic and sociocultural competence.Sociolinguistics serves as a bridge between linguistic knowledge and practical communication skills, emphasizing its importance in preparing students for real-life communicative situations.